2005
DOI: 10.1002/pssc.200461219
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient to hydrogen permeability palladium membranes supported in porous silicon

Abstract: Hydrogen separation from gas mixtures and purification are of great importance and interest. Technologies based on the use of metallic membranes are the most suitable ones for these purposes. Pd and its alloys with Ag, Au, Cu and Ni are the best candidates for the membranes. In the present work, technology of the membranes formation based on macroporous silicon with Pd/Ag thin film has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A broad range of porous supports have been investigated over the years such as alumina [6], silicon [7], nickel [8], glass [9] and stainless steel [10]. Porous stainless steel (PSS) substrates are the preferred choice for supporting Pd alloys due to their strength, robustness, similar thermal expansion coefficient as well as ease of welding and sealing [11].…”
Section: Introductionmentioning
confidence: 99%
“…A broad range of porous supports have been investigated over the years such as alumina [6], silicon [7], nickel [8], glass [9] and stainless steel [10]. Porous stainless steel (PSS) substrates are the preferred choice for supporting Pd alloys due to their strength, robustness, similar thermal expansion coefficient as well as ease of welding and sealing [11].…”
Section: Introductionmentioning
confidence: 99%
“…2 Due to the characteristics and features, the applications range from capacitors, 3 microsystem technologies, 4 electrode materials, 5 solar cells, 6 and fuel cells 7 to membranes. 8 PS is usually produced by the application of low anodic bias ͑up to 200 mV͒ on the silicon substrate immersed in a hydrofluoric acid ͑HF͒ solution. 9 PS is also formed in organic electrolytes containing HF while water, originated from HF ͑48-49%͒, is usually included in the electrolyte.…”
mentioning
confidence: 99%
“…Moreover, the nanoporous layer on the surface of the porous layer is not observed with the investigated silicon wafers p -type conductivity in a wide range of resistivity's. 8 Therefore, to form deep GPS-var layers, one should use "anhydrous" electrolytes. In addition, the processing in the water should be excluded from the sample manufacturing process after the formation of the reinforced layer.…”
Section: Formation Of Gradient-porous Silicon Structures With Variabl...mentioning
confidence: 99%
“…It was shown that for this purpose, the dependence of the pore diameter on the ingredient composition of the electrolyte or the change in the anode current density during the etching process can be used. 7,8 By increasing the diameter at the bottom in such a way that there is a continuous overlap of the adjacent pores, it is possible to separate the porous layer from the substrate. 8 Using these methods, membranes with a diameter of 1.5 cm and a thickness of up to 75 μm were formed.…”
mentioning
confidence: 99%
See 1 more Smart Citation